Political Economic Approach to Old Age: The Carroll Estes Model - Elif Çevik (Senectus)
Aging, a crucial concern within social policy and services, has gained increasing attention from scholars and policymakers because of the accelerating global demographic shift toward the aging population. Despite this, postgraduate studies on aging within Turkey’s social policy and services field remain notably low. Moreover, existing studies predominantly adopt a structural-functional approach, lacking critical analysis. Thus, this article addresses this gap by introducing a critical perspective, notably lacking in current Turkish academic discourse on aging studies. To this end, Carroll Estes’ model, exemplifying such criticality, is presented comprehensively for the first time in Turkish academia. Estes’ model delves into the central phenomenon of aging at both macro and micro levels, scrutinizing ideology, the state, gender system, postindustrial capitalism, globalization, the medical-industrial complex, and elderly care initiatives at the macro level. At the micro level, it examines interlocking systems of oppression, class, race/ethnicity, gender, and citizenship. This multifaceted model promises to enrich various disciplines, particularly social policy, social services, and sociology, offering researchers a broader lens for understanding and analyzing the complexities of aging.